重建参数对CT肺结节容积测量的影响 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: It has been proven that volumetric measurements could detect subtle changes in small pulmonary nodules in serial CT scans, and thus may play an important role in the follow-up of indeterminate pulmonary nodules and in differentiating malignant nodules from benign nodules. The current study aims to evaluate the effects of different reconstruction parameters on the volumetric measurements of pulmonary nodules in chest CT scans. METHODS: Thirty subjects who underwent chest CT scan because of indeterminate pulmonary nodules in General Hospital of Tianjin Medical University from December 2009 to August 2011 were retrospectively analyzed. A total of 52 pulmonary nodules were included, and all CT data were reconstructed using three reconstruction algorithms and three slice thicknesses. The volumetric measurements of the nodules were performed using the advanced lung analysis (ALA) software. The effects of the reconstruction algorithms, slice thicknesses, and nodule diameters on the volumetric measurements were assessed using the multivariate analysis of variance for repeated measures, the correlation analysis, and the Bland-Altman method. RESULTS: The reconstruction algorithms (F=13.6, P < 0.001) and slice thicknesses (F=4.4, P=0.02) had significant effects on the measured volume of pulmonary nodules. In addition, the coefficients of variation of nine measurements were inversely related with nodule diameter (r=-0.814, P < 0.001). The volume measured at the 2.5 mm slice thickness had poor agreement with the volumes measured at 1.25 mm and 0.625 mm, respectively. Moreover, the best agreement was achieved between the slice thicknesses of 1.25 mm and 0.625 mm using the bone algorithm. CONCLUSION: Reconstruction algorithms and slice thicknesses have significant impacts on the volumetric measurements of lung nodules, especially for the small nodules. Therefore, the reconstruction setting in serial CT scans should be consistent in the follow-up of indeterminate pulmonary nodules, more importantly for the small nodules.